Management of Septic Non-Union - جوني أحمد (Latakia University Journal -Medical Sciences Series, 2020)
This study included (154) patients with septic non-unions of different bones of extremities, most conditions were followed by war injuries (66.23%). All patients were operated within two stages operations with 3 months interval. The primary aim was infection control firstly; the secondary aim was bone consolidation. Local injection of antibiotics was used at both stages, the external fixation was the choice in all conditions, and all patients were undergone physical therapy. The method used in our study enabled control of infection, callus formation within a short period of rime, while maintaining the function of the injured limp in most cases. Positive results were recorded in (89.6%), and were negative in (10.4%).